A real-world retrospective study of safety, efficacy, compliance and cost of combination treatment with rush immunotherapy plus one dose of pretreatment anti-IgE in Chinese children with respiratory allergies - Zhang, Pingping; Bian, Sainan; Wang, Xibin; Chen, Zhuanggui; Yang, Lifen; Xiao, Feng; Guan, Kai (Frontiers in Immunology, 2022)
Background: The efficacy of allergen immunotherapy (AIT) in treating pediatric allergy has been clearly demonstrated, however, many patients hesitate to initiate AIT due to weekly hospital visits during the 3-4 month up-dosing phase. Meanwhile, rush immunotherapy (RIT) shortens the duration of the up-dosing phase to 7 days. However, considering that patients receiving RIT are exposed to the allergens during a much shorter period of time and thus may be at greater risk of systemic reactions, RIT is currently underused, especially in children. This study investigated the utility of combination treatment with RIT plus 1 dose of pretreatment anti-IgE in children with respiratory allergies. Methods: In this retrospective study, we reviewed records of children with AR and/or AA sensitized to dust mite allergens receiving RIT+1 dose of pretreatment anti-IgE (the RIT group) or conventional immunotherapy (the CIT group) at our hospital from January 2020 to March 2021. Data such as visual analogue scale (VAS) scores, comprehensive symptom and medication score (CSMS), allergy blood test results, adverse reactions, compliance and cost were collected and analyzed. Results: 40 patients in the RIT group and 81 patients in the CIT group were included in this study. Both treatments were well tolerated and patients in the 2 treatment groups had comparable local and systemic reactions. Compared to CIT, RIT + anti-IgE combination led to significantly faster symptomatic improvement as demonstrated by significantly decreased VAS and CSMS starting as early as 1 month after AIT initiation (P<0.05). Nobody dropped out in the RIT group during the 1 year follow-up, while 11 out of 81 patients in the CIT group dropped out (loss rate 13.5%). Thus, the RIT group had significantly higher compliance rate than the CIT group (P<0.05). Finally, the 2 treatment regimens had comparable cost per patient per injection (P> 0.05). Conclusions: RIT + 1 dose of pretreatment anti-IgE combination has practical advantages over CIT, including comparable safety, better compliance, and probably a faster onset of clinical efficacy at no additional cost, so it can be an useful regimen for the treatment of Chinese children with respiratory allergies.